Managing Diversity, Rewriting Memory: A Historical Perspective on Religious Pluralism and Conflict in Indonesia - Rumadi (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2025)
This paper explores how the Indonesian government—especially at the local level—has historically engaged in resolving religious freedom-related conflicts. Unlike most studies that trace the roots of religious violence to ideological tensions between religion and the state, this research focuses on the actual mechanisms of conflict resolution and reconciliation, particularly in the post-Reformasi period when decentralization redefined governance structures. It argues that religious conflict resolution in Indonesia is shaped less by normative ideals of religious freedom and more by pragmatic political calculations and the pursuit of social recognition. Local governments often broker informal agreements aimed at preserving public order, without challenging dominant religious ideologies or addressing structural discrimination. Grounded in a socio-historical approach, this study analyzes three prolonged religious conflict cases: the displacement of Shi’ite communities in Sampang, the forced relocation of Ahmadis in West Nusa Tenggara, and the church permit dispute involving GKI Yasmin in Bogor. Data were collected through interviews, field observations, media analysis, and official documents. The findings suggest that reconciliation processes in Indonesia are contingent, varied, and shaped by local political contexts. While some local leaders play constructive roles in de-escalation and facilitating return or relocation, others repro duce discrimination or tolerate intolerant groups. This paper concludes that religious conflict resolution in Indonesia is a historically contingent and politically mediated process. It reflects broader tensions between democratic ideals and the persistence of majoritarian religious politics. Recognition—understood not as identity politics but as constitutional inclusion—emerges as a foundational principle for reconciliation and plural coexistence.